Astrocyte focal adhesion kinase reduces passive stress coping by inhibiting ciliary neurotrophic factor only in female mice - Cuihong Jia; W. Drew Gill; Chiharu Lovins; Russell W. Brown; Theo Hagg (Neurobiology of Stress, 2024)
Astrocytes have been implicated in stress responses and produce ciliary neurotrophic factor (CNTF), which we have shown in the mouse medial amygdala (MeA) to promote passive stress coping response only in females. Pharmacological inhibition of focal adhesion kinase (FAK) upregulates CNTF expression. Here, we found that inducible knockout of FAK in astrocytes or systemic treatment with an FAK inhibitor increased passive coping behavior, i.e., immobility, in an acute forced swim stress test in female, but not male, mice. Strikingly, four weeks of chronic unpredictable stress (CUS) did not further increase passive coping in female astrocytic FAK knockout mice, whereas it exacerbated it in female wildtype mice and male mice of both genotypes. These data suggest that astrocyte FAK inhibition is required for chronic stress-induced passive coping in females. Indeed, CUS reduced phospho-FAK and increased CNTF in the female MeA. Progesterone treatment after ovariectomy activated amygdala FAK and alleviated ovariectomy-induced passive coping in wildtype, but not astrocytic FAK knockout females. This suggests that progesterone-mediated activation of FAK in astrocytes reduces female stress responses. Finally, astrocytic FAK knockout or FAK inhibitor treatment increased CNTF expression in the MeA of both sexes, although not in the hippocampus. As mentioned, MeA CNTF promotes stress responses only in females, which may explain the female-specific role of astrocytic FAK inhibition. Together, this study reveals a novel female-specific progesterone-astrocytic FAK pathway that counteracts CNTF-mediated stress responses and points to opportunities for developing treatments for stress-related disorders in women.